2015
DOI: 10.1016/j.ijgo.2015.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of HPV infection among women in Ningbo, China

Abstract: In Ningbo, many women with cervical cytologic abnormalities have HPV infection. Vaccines targeting HPV52 and HPV58 in conjunction with HPV16 and HPV18 are required for the prevention and treatment of cervical lesions in Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
6
21
0
Order By: Relevance
“…However, these issues are outside the scope of this epidemiological study. Further comparative analysis showed that HPV16, 52, and 58 are the three most dominant high-risk HPV strains in five Chinese reports, although the order of prevalence rates from high to low varied widely and other genotype distributions also differed regionally in China [21][22][23][24][25]. Other data from India, Northern Ireland, the USA and integrated data varied except for HPV16, which remained a dominant strain worldwide [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, these issues are outside the scope of this epidemiological study. Further comparative analysis showed that HPV16, 52, and 58 are the three most dominant high-risk HPV strains in five Chinese reports, although the order of prevalence rates from high to low varied widely and other genotype distributions also differed regionally in China [21][22][23][24][25]. Other data from India, Northern Ireland, the USA and integrated data varied except for HPV16, which remained a dominant strain worldwide [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 98%
“…Both the quadrivalent and bivalent vaccines protect against HPV types 16 and 18, which cause 70% of cervical cancers; the quadrivalent vaccine also protects against HPV types 6 and 11, which cause 90% of genital wart cases [33]. Although it is difficult to map the HPV genotype distribution and prevalence, large amounts of data indicate that HPV genotype distribution varies largely across regions [21][22][23][24][25][26][27][28][29][30]. Thus, regional HPV surveillance is essential for effective vaccination and HPV-related cancer control and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…These last interventions are most important, particularly in HIV-positive women, where the HPV-vaccination yet must be shown to be efficacious in HIV-infected individuals (20) particularly in the group with a CD4 count inferior to 500 cell/mm 3 . Secondly, another interesting aspect about vaccines issues from our study: the currently marketed vaccines do not provide total coverage against HPV infections; in fact, for the great variability of HPV circulating genotypes, not all most frequently circulating genotypes are included in 2-or 4-valent HPV vaccines (22)(23)(24) such as genotypes 31, more frequent in HIV-positive women, and 52/58, more frequent in healthy women. This variability may be particularly dangerous in HIV-positive women where there is an increased risk of H-SIL and invasive cervical cancer related also to other HPV-genotypes different from HPV-16 and -18.…”
Section: Group 1 (Hiv Negative) Group 2 (Hiv Positive) --------------mentioning
confidence: 97%
“…In China, a pooled analysis of 17 population-based studies, including 30,207 females, identified the HPV prevalence to be 17.7% (50). Furthermore, a province-wide study was conducted in Ningbo province which identified 185 of 1,373 females aged between 22 and 64 years (13.5%) as HPV-positive and the prevalence rates were 13.8, 8.8 and 7.9% in Shenzhen, Xinjiang and Chaozhou, respectively (5154). The papillomavirus family is heterogeneous and highly species-specific.…”
Section: Ovarian Carcinogenesis and Microorganismsmentioning
confidence: 99%